SMART ECONOMIC DEVELOPMENT WITHIN EUROPEAN COUNTRIES - Popović, Andrija; Ivanovic Djukic, Maja; Milijic, Ana (The European Journal of Applied Economics, 2022)
An Industry 4.0 is a set of digital and physical technologies and cyber-physical systems that offer new values to the economy’s macro and micro levels. It is causing significant changes and developments in the industrial sector worldwide. This research aims to determine the impact of Industry 4.0 on socio-economic development by establishing the correlation between Industry 4.0 Index and the UNDP Human Development Index (HDI). Following the correlation analysis, the country cluster will be formed based on the implementation of the I4.0 and socio-economic development. There is a strong correlation between Industry 4.0 implementation and socio-economic development on the European level, while all countries can be placed within three significant clusters. This paper confirms the positive impact of Industry 4.0 on socio-economic development. It also provides institutional and business stakeholders with an objective incentive to implement the core I4.0 technologies faster.